Smart-in-Car Sensing - Jabari, Mohammed; Alrefaya, Mousa (The 6th International Conference on Innovation in Science and Technology, 2019)
Abstract—The widespread use of smartphones with their huge processing capabilities and the array of sensors they are shipped with, in addition to their mobility feature, have all opened the door for a multitude of applications in an unprecedented way. The fact that most drivers these days carry their smartphones with them presents a great opportunity to develop a new type of applications that harvest and interpret the tremendous amount of data smartphones’ sensors collect. Smart-in-car sensing uses smartphones’ sensors to collect car’s movement data and puts it into context in a smart way that helps the driver. Smart-in-car sensing presents smart solutions to a number of today’s problems faced by drivers. One of the problems smartphones can help solve is traffic congestion. Fuel economy driving is another goal smartphones can help drivers achieve. Combining that with a solution to traffic congestion can contribute to low carbon dioxide emissions. A smooth and comfortable drive is something else smartphones sensors can help the drivers achieve. Moreover, smart-in-car sensing can prevent drowsy driving, which is a major cause of accidents. Furthermore, context-aware data provided by smart-in-car sensing is a gold mine of information that stakeholders can use to make better plans and to further the transition to smart cities. The proposed android application uses smartphones’ accelerometer sensor to detect major events the car driver encounters during his daily drive. The application has to deal with many challenges, one of these is the fact that sensors’ data, especially the accelerometer, produces too much noise, and to make use of the sensor’s data there must be a way to filter out unwanted components of the data. Moreover, even low power sensors, like the accelerometer, in the fastest mode, can put considerable power demands on the smartphone’s battery. Interpreting sensors’ data and putting it into context is also a great challenge. The application was able to detect road bumps, driving behavior, and the effect of aggressive driving on the fuel consumption of the car. Moreover, the application can detect when a car enters a traffic jam, geotagging the location of the traffic jam, and share it with other drivers or simply upload it to the cloud.
Keywords: Smartphones, Sensors, Cars, Accelerometer, Mobile Apps